Cerebellar contributions to fear-based emotional processing: relevance to understanding the neural circuits involved in autism - Couto-Ovejero, Sabina; Ye, Jingjing; Kind, Peter C.; Till, Sally M.; Watson, Thomas C. (Frontiers in Systems Neuroscience, 2023)
Cerebellar networks have traditionally been linked to sensorimotor control. However, a large body of evidence suggests that cerebellar functions extend to non-motor realms, such as fear-based emotional processing and that these functions are supported by interactions with a wide range of brain structures. Research related to the cerebellar contributions to emotional processing has focussed primarily on the use of well-constrained conditioning paradigms in both human and non-human subjects. From these studies, cerebellar circuits appear to be critically involved in both conditioned and unconditioned responses to threatening stimuli in addition to encoding and storage of fear memory. It has been hypothesised that the computational mechanism underlying this contribution may involve internal models, where errors between actual and expected outcomes are computed within the circuitry of the cerebellum. From a clinical perspective, cerebellar abnormalities have been consistently linked to neurodevelopmental disorders, including autism. Importantly, atypical adaptive behaviour and heightened anxiety are also common amongst autistic individuals. In this review, we provide an overview of the current anatomical, physiological and theoretical understanding of cerebellar contributions to fear-based emotional processing to foster further insights into the neural circuitry underlying emotional dysregulation observed in people with autism.